The Conundrum and Promise of Intercultural Theology in the Western Academy - Toren, Bernard van den (International bulletin of mission research, 2024)
Intercultural theology has a dual origin. On the one hand it derives from the development of diverse forms of theologizing in Christianity worldwide, while on the other hand it originates in the North Atlantic university where intercultural theology and world Christianity have developed as particular fields of study. With reference to two examples of spiritual possession and biblical interpretation, this article argues that its location within Western academic institutional settings presents obstacles to the ability of intercultural theologians in the West to do justice to the proper nature of various forms of theologizing in other contexts. In particular, attention is drawn to the fragmentation of theological disciplines, the secularization of academic discourse, the use of cultural analysis, and the power of the Western academy. The article concludes with some proposals regarding how an awareness of this dual origin can help intercultural theologians to be a critical presence within the Western academy beyond their discipline.